Podatność polskich proweniencji i rodów dębu szypułkowego (Quercus robur L.) na zasiedlenie przez Phytophthora cambivora - Jankowiak, Robert; Balonek, Angelika; Banach, Jacek (Leśne Prace Badawcze, 2013)
Phytophthora cambivora (Straminipila, Oomycota) causes root rot and stem canker on several deciduous tree species in Europe. However, very little is known about the variation in susceptibility to P. cambivora colonization among provenances and families of pedunculate oak ( Quercus robur L .). We studied variation in susceptibility of one French and 16 Polish provenances, representing 62 families. Samples were taken from three test plots located in the Brzesko Forest District. Oak susceptibility to P. cambivora was assessed by measuring lesion length following inoculation of excised shoots with two isolates of P. cambivora . There was significant variability in susceptibility among the 17 provenances tested. The highest susceptibility to P. cambivora was apparent in several provenances including Tronçais, Zaporowo, Runowo, Opole, and Krotoszyn; while the most resistant provenances originated from Chojnów, Siedlce, Płock, Krotoszyn-90 and Wioska. There was also significant within-provenances variation in susceptibility to P. cambivora .